(untitled) (Proceedings of the European Wave and Tidal Energy Conference, 2025)
This study aims to design and optimise tidal lagoon schemes in Wales, focusing on three case studies: North Wales Tidal Lagoon, Cardiff Tidal Lagoon, and Newport Tidal Lagoon. By integrating genetic algorithms with traditional 0-D methodologies, the research optimises design parameters and turbine selection while exploring flexible operational schemes to significantly enhance energy output and economic performance. Additionally, it examines the long-term performance of these systems under climate change scenarios for the years 2085, 2135, and 2185, providing insights into future resilience and adaptability. The modelling outcomes will also inform evaluations of supply chain dynamics and economic feasibility. This study highlights the potential of tidal lagoon developments in enhancing energy generation, storage, and economic benefits, contributing to a sustainable and resilient energy future for the UK and beyond.